Numerical Investigation of Over Fire Air (OFA) Effect on Flow Characteristics, NOx Combustion and Emission in a 600 Mw Tangentially Fired Pulverized Coal Boiler - Eka Setiawan Seputro; Bambang Sudarmanta (IPTEK The Journal of Engineering, 2019)
One of the coal-fired air emissions in boilers is NOx, which has a significant impact on the environment and could cause acid rain, ozone formation, visual impairment and health problems in humans. There are several technologies to reduce and control the formation of NOx emissions, which one of these technologies is the use of over-fire air (OFA). In this research will observe the effect of overfire air (OFA) usage and analyze by numerical 3D modeling method using computational fluid dynamics (CFD) in Paiton 9 power plant boiler and analyzed for 5 (five) OFA damper opening variations, i.e 0%, 25%, 50 %, 75% and 100%. This research will analyze several factors that have significant influence on NOx emission formation, that are: the temperature distribution of the boiler during the combustion process, the distribution of nitrogen oxide (NO) and carbon dioxide (CO2), direction of flue gas flow and trajectory of coal particles and residence time indicating the length of time of burning. The results showed that the lower the flame temperature, the smaller the formation of NOx; the smaller the oxygen content in the combustion process, the smaller the formation of NOx; the shorter the residence time of combustion products in the high temperature zone the smaller the formation of NOx, and the smaller the nitrogen content in coal, the smaller the formation of NOx.